Normalização e tecnologização: uma perspectiva acerca da legitimação política do direito - Reis, Rodrigo Ferlin Saccomani dos (2016)
Using Michel Foucault´s "analytics of power” as a premise, we tried to access the question concerning the legitimation of “technologized law”, a concept by Tércio Sampaio Ferraz Junior. From the perspective that legal dogmas have become disconnected from external references, this philosopher of law understands that law loses its reference to justice becoming a designation of arbitrary will. In turn, assuming truth as a political issue, Michel Foucault lays the foundations for a method of analyzing the operation of power, in which it is exercised through the production of subjects and subjectivities. In this proposed confrontation, the study of "power-knowledge" relations, as brought by Foucault, allow us to highlight the political aspect of law, and of the disputes revolving around it, so it is through this internal relationship, which incorporate the rules of the legal game within the rules of a political game that extrapolates its scope, that we will discuss the political legitimacy of law